Bioconversion of ω-fatty acid from giant snakehead (Channa micropeltes) fish oil - Omar, Muhammad Nor; Md Yusoff , Nur Shahidatul Ahlam; Zainuddin, Nur Aziyah; Zuberdi, Ahmad Muzammil (Oriental Scientific Publishing Co., 2014)

(untitled)
Study on bioconversion of ω-fatty acids extracted from giant snakehead (Channa micropeltes) fish oil was carried out using guinea pig lung homogenate. The fish oil, after hydrolysis to their fatty acids, was incubated aerobically at 37oC in phosphate buffer solution with the addition of guinea pig lung homogenate. After incubation and chemoreduction, it was found that ca. 76% arachidonic acid has been converted to the prostaglandin, PGE1. The fatty acid constituents in fish oil were analysed by GC-MS after methylation.